Perancangan Sistem Kendali Motor DC Berbasis Suhu Menggunakan Logika Perangkat Keras - Eric Gamaliel Gurusinga; Taruna Anugrah Lase; Noel Elpidos Bernard (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This study aims to design and simulate a temperature-based three-level DC motor speed control system using non-programmable hardware logic as an alternative that does not depend on a microcontroller. The system is built through a step-by-step circuit, namely the LM35 temperature sensor detects changes in environmental temperature, the signal is conditioned by an LM358 operational amplifier with a non-inverting configuration and a gain of 3.2 times, then digitized by an ADC0804 type Analog-to-Digital Converter (ADC) with a resolution of 10 mV/LSB, and translated by a 3-to-8 line 74HC238 decoder to activate three relays that regulate the external resistance of the motor drive. Testing is carried out through simulations on Proteus VSM software with temperature variations of 25°C to 80°C. Simulation results show that the system is able to maintain standby mode below 30°C and gradually switch to Level 1 (2340 RPM), Level 2 (2800 RPM), and Level 3 (3500 RPM) according to the set temperature threshold, with the entire signal path from the sensor to the relay actuation operating synchronously without any program code intervention. The back EMF also affects the actual terminal voltage of the motor, but the stability of the speed transition is maintained at each level. This study proves that the non-programmable hardware logic approach is feasible as a reliable and simple temperature control solution.